Application of cyclone technology in paste backfill plant design - Landriault, J; Primeau, PA (Paste 2013: Proceedings of the 16th International Seminar on Paste and Thickened Tailings, 2013)
Historically cyclone technology has been used for classification and dewatering purposes in mineral processing. It has also been extensively used in the preparation of suitable material for hydraulic backfill. Conversely when it comes to paste backfill plant design, thickening and filtration technology is typically used, and where high backfill strength is required, classified aggregate is often added. These are viable and accepted practices for the preparation of paste backfill; however, in certain applications the use of cyclones within the paste preparation process provides alternatives which can result in lower capital and/or operating cost for the paste backfill system. This paper will present novel applications of cyclone classification and dewatering technologies in the preparation of paste backfill. Specifically, the paper will discuss how cyclones can be used in certain applications to dewater the tailings without the need for thickeners, thereby lowering the capital cost and/or reducing the cement binder requirements and consequently lowering the operating cost. Examples of projects where the use of cyclone classification was considered during the development of the process flow sheet highlights the drivers for its incorporation in the resulting paste backfill systems.